The Early Cretaceous Zaduo Granite, Eastern Qiangtang Terrane (China)—An Attempt to Constrain its Paleolatitude and Tectonic Implications - Fu, Qiang; Yan, Maodu; Dekkers, Mark J.; Guan, Chong; de Boer, Rosa A.; Yu, Liang; Xu, Wanlong; Li, Bingshuai; Shen, Miaomiao; Zhang, Jingyu; Xu, Zunbo (Frontiers in Earth Science, 2022)
The Eastern Qiangtang Terrane is an orogenic-like belt around the Eastern Himalayan syntaxis (EHS). The deformation history of this terrane must be known to understand how the EHS region responded to the Lhasa-Qiangtang collision and the closure of the Bangong-Nujiang Ocean (BNO). Here, we present a new paleomagnetic investigation on the Early Cretaceous granite (~126 Ma) in the Zaduo area, Eastern Qiangtang Terrane. Petrographic observations reflect crystallization from primary melts with only limited subsequent alteration (chloritization of biotite). Magnetite appears to be the dominant carrier of the characteristic remanent magnetization (ChRM) based on stepwise demagnetization of the natural remanent magnetization, supplemented by detailed rock magnetic measurements, including magnetization versus temperature, and acquisition curves of the isothermal and anhysteretic remanent magnetization. End-member modeling of those acquisition curves helped constrain the paleomagnetic analysis. The inconsistent demagnetization behavior between AF at high demagnetization levels and thermal demagnetization was attributed to development of gyroremanent magnetization in the AF demagnetization generated by fine-grained single domain magnetite. The ChRM directions from 92 granite samples in geographic coordinates yield an average of declination Dg of 2.6° and inclination Ig of 38.6°, α95 = 2.1°. The amount of tilting of the granite is poorly constrained which makes proper correction rather tedious. We compared the expected bedding attitudes (Strikeexp=43.1°, Dipexp =46.1°) derived from published data with the average observed bedding attitudes (Strikeobs=54°, Dipobs =32°) of the Middle-Upper Jurassic sandstones of the Yanshiping group that was intruded by the Early Cretaceous granite. The discrepancy between expected and measured bedding attitudes implies that the Jurassic strata in the Zaduo area were already tilted prior to the intrusion of the ~126 Myr Zaduo granite, which was attributed to the Lhasa-Qiangtang collision and the closure of the BNO. The collision led to a series of geological events, such as the tilting of the strata, the ophiolite emplacement, the development of a peripheral foreland basin, and the magmatic activity gap. The tilting/folding of the strata was generally delayed by the layer parallel shortening processes during the early stages of the deformation, thus suggesting an older Lhasa-Qiangtang collision (i.e. >126 Ma).